Etno-epistemologi Kearifan Lokal Melayu Jambi sebagai Respons terhadap Pandemi Covid-19 - M. Ied Al Munir; Zaki Mubarak; Nazar Husain Hadi Pranata Wibawa (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This research aims to elaborate on the importance of local wisdom for the Jambi Malay community, both in understanding and responding to the COVID-19 pandemic. This research is a field research that has used qualitative methods where data has been collected through interviews, observation, documentation and FGD. The data that has been collected is sorted through data condensation, data presentation and drawing conclusions. After that, the data has been analyzed with epistemological theory. Research has found that there is a fundamental difference between the epistemology of the government and the epistemology of the Jambi Malay community in the form of ethno-epistemology. This difference has led to differences in understanding and response by government and society. This finding has at the same time answered the research objective that local wisdom is important for the Jambi Malay community in understanding and responding to the COVID-19 pandemic